Pengaruh Penggunaan Aplikasi Wellingbom 2.0 terhadap Kemampuan Suami Mendeteksi Dini Kehamilan Risiko Tinggi - Pratamaningtyas, Susanti; Titisari, Ira (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: The COVID-19 pandemic has a significant impact on the health sector. In Kediri, pregnant women have limited access to checking their conditions. Many high-risk pregnancies are happening, especially in the Sukorame area. It makes the family, especially the husband, should pay more attention to his wife’s pregnancy. However, husbands often have no idea about pregnancy, including how to detect early high-risk pregnancy conditions. It often leads to delays in handling this problem. This study aimed to determine the effect of using The Wellingbom 2.0 Application on husbands' ability to detect early high-risk pregnancies.Method: This study used a research and development design with a descriptive and quasi-experiment approach. The population was 100 people. Samples were 80 people using incidental sampling techniques with the inclusion criteria were husbands of pregnant women who live in the working area of Sukorame Health Center and have an android-based smartphone, also they must be able to operate it. The data that have been collected were conducted normality test and then tested using Wilcoxon match pair statistic test by SPSS 16.00. Respondents pretested and were given an application for one week, after which the posttest was done.Results: The result of the normality test showed p-values of 0.004 for pretest and 0.000 for posttest, this indicates abnormally distributed data. Further analyzed using non-parametric sample Wilcoxon 2-paired test showed p-value 0.000, which means Ha accepted. It showed a significant change in respondents' ability to perform early detection to high-risk pregnancy after using the wellingbom 2.0 application. It would be better if husbands were also being educated about high-risk pregnancies to increase their awareness of their wives’ pregnancies.